2018
DOI: 10.1111/liv.13975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hepatitis B virus (HBV) surface‐gene variability on markers of replication during treated human immunodeficiency virus‐HBV infection in Western Africa

Abstract: Background & Aims Replication markers exhibit substantial variation during chronic hepatitis B virus (HBV) infection, part of which can be explained by mutations on the surface (S) gene. We aimed to identify S‐gene mutations possibly influencing the quantification of HBV replication markers (MUPIQH) in HBV genotype E infection, common to Western Africa. Methods Seventy‐three antiretroviral treatment (ART)‐naïve human immunodeficiency virus (HIV)‐HBV co‐infected patients from Côte d'Ivoire, initiating anti‐HBV‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Indeed, several studies have demonstrated that decreased genetic complexity, less frequent or specific mutations, and less frequent deletions in the “a” determinant are correlated with clearing HBsAg [ 60 , 61 , 62 ]. One study has examined the broader spectrum of S -gene mutations in co-infected individuals prior to initiating anti-HBV containing ART, including mutations on the “a” determinant, and failed to find any mutations linked to HBsAg-seroclearance [ 63 ]. Hence, S -gene mutations might not affect rates of HBsAg-seroclearance during treatment.…”
Section: Determinants Of Functional Cure During Treated Hiv-hbv Co-infectionmentioning
confidence: 99%
“…Indeed, several studies have demonstrated that decreased genetic complexity, less frequent or specific mutations, and less frequent deletions in the “a” determinant are correlated with clearing HBsAg [ 60 , 61 , 62 ]. One study has examined the broader spectrum of S -gene mutations in co-infected individuals prior to initiating anti-HBV containing ART, including mutations on the “a” determinant, and failed to find any mutations linked to HBsAg-seroclearance [ 63 ]. Hence, S -gene mutations might not affect rates of HBsAg-seroclearance during treatment.…”
Section: Determinants Of Functional Cure During Treated Hiv-hbv Co-infectionmentioning
confidence: 99%
“…In cohort studies of people with HIV in the U.S., where HBV is not endemic, the most common HBV subgroup noted was non‐immune/vaccinated (66–74%) followed by resolved HBV infection (20–23%) and isolated anti‐HBcAb (3.5–6%) 6,17 . Possible explanations for these observed subgroup differences among people with past or present HBV infection include: (1) timing of HBV infection, with co‐infected individuals in sub‐Saharan Africa being mostly infected with HBV long before HIV infection and co‐infected individuals in the U.S. more likely to be in the ‘window phase’ of acute HBV infection; (2) immunologic differences, which may produce a different proportion of individuals due to the timing of waning anti‐HBsAb levels following resolved HBV infection; and to a lesser extent (3) genetic differences in HBV, which may result in HBsAg that escapes detection due to mutations on the surface gene 37 …”
Section: Discussionmentioning
confidence: 99%